Akpan and the Smugglers - Uwemedimo, Rosemary (Pilgrim Books Ltd, 1965)
When his father was arrested for smuggling, Akpan went all out to prove his innocence. In the process, he uncovered the smugglers' gang.
Keywords: Juvenile Fiction